Specific leaf mass, fresh: dry weight ratio, sugar and protein contents in species of Lamiaceae from different light environments - Castrillo, M. (2005)
Samples from eleven species of Lamiaceae were collected from different light environments in Venezuela for laboratory analysis. The studied species were: Plectranthus scutellarioides (Ps), Scutellaria purpurascens (Sp), Hyptis pectinata (Hp), H. sinuata (Hs), Leonorus japonicus (Lj), Plecthranthus amboinicus (Pa) Ocimum basilicum (Ocb), O. campechianum (Occ) Origanum majorana (Orm), Rosmarinus officinali, (Ro) and Salvia officinalis (So). Protein and soluble sugar contents per unit of area were measured, Specific Leaf Mass (SLM) and fresh:dry weight (FW/DW) ratios were calculated. The higher values for soluble sugars contents were present in sun species: Lj, Pa, Ocb, Occ, Or.m, Ro and So; the lower values were obtained in low light species: Ps , Sp , Hp, Hs. The values of protein content do not show any clear trend or difference between sun and shade environments. The lowest values for the fresh weight: dry weight ratio are observed in sun species with the exception of Lj and Pa, while the highest value is observed in Pa, a succulent plant. The higher values of specific leaf mass (SLM) (Kg DMm-2) are observed in sun plants. The two way ANOVA revealed that there were significant differences among species and between sun and low light environments for sugar content and FW:DW ratio, while SLM was significant for environments but no significant for species, and not significant for protein for both species and environments. The soluble sugar content, FW:DW ratio and SLM values obtained in this work, show a clear separation between sun and shade plants. The sugar content and FW:DW ratio are distinctive within the species, and the light environment affected sugar content, FW:DW ratio and SLM. These species may be shadetolerant and able to survive in sunny environments. Perhaps these species originated in shaded environments and have been adapting to sunny habitats.